Penalty patterns regarding the application of restorative justice in the resolution of embezzer cases in off - Seno Gumbira; Muhammad Karim; Irsanti Asih; Solikhah; Liana Susanti (Journal of Law Science, 2024)
The pattern of punishment is the basis of the question of why someone is convicted or not convicted for the criminal law maker. Restorative justice is a legal product that prioritises the recovery of victims, perpetrators, and related communities in minor criminal cases as stated in the Regulation of the Chief of the Indonesian National Police Number 8 of 2021. However, the Criminal Investigation Unit of the Bangka Resort Police was able to resolve a case of embezzlement in office that allegedly violated Article 374 of the Criminal Code by using a restorative justice approach. This study aims to determine the investigator's consideration in applying restorative justice in embezzlement cases in Bangka Police Criminal Investigation Unit and the pattern of punishment. The research method used is juridical- empirical with a statutory approach and a case approach. The consideration of investigators in applying restorative justice in cases of embezzlement in office at Satreskrim Polres Bangka is the revocation of the report from the reporting party with an amicable agreement and the reported party is willing to compensate for the losses caused by his actions and the reported party is not a recidivist. The pattern of punishment for the application of restorative justice in the settlement of embezzlement cases in this position is based on the aim of restoring the parties by considering the awareness, responsibility, and peaceful agreement of the parties which is more beneficial than the punishment that should be received and getting their rights and obligations fairly